Paper useful as thermal insulation and fire protection for battery cells
A paper-based flame barrier and insulation material with fibrids, mica, and airgel powder addresses particle shedding issues and enhances thermal insulation and flame protection in battery packs, preventing thermal runaway and fires.
Patent Information
- Application Number
- JP2021555622
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2019-03-15
- Filing Date
- 2020-03-11
- Publication Date
- 2024-12-25
- Estimated Expiration
- 2040-03-11
AI Technical Summary
Existing battery insulation materials shed particles, causing dust and misalignment issues, and fail to effectively prevent thermal runaway and fires in battery packs.
A paper-based flame barrier and insulation material composed of 40-70% fibrids, 30-60% mica, and 20-80% airgel powder, with a thickness of 100-4000 micrometers, providing improved thermal insulation and flame retardancy without shedding.
The material effectively prevents thermal energy propagation between battery cells, maintaining adjacent cells below 200°C and offering enhanced flame protection, with reduced particle shedding and improved adhesion, thus preventing fires and explosions.
Smart Images

Figure 0007606467000005 
Figure 0007606467000006 
Figure 0007606467000007
Abstract
Description
[Technical field]
[0001] The present invention relates to a paper that is useful as a flame breaker for batteries and as flame retardant thermal insulation between cells, and to batteries containing the paper. [Background technology]
[0002] With the expanding use of lithium-ion and other batteries in electric vehicles, there has been a noticeable increase in battery failures, including overheating and fires. Flame barriers and flame-retardant insulation are required to separate battery cells to prevent overheating and hot spots in one cell from causing thermal runaway that could result in fire or explosion in the entire battery pack.
[0003] Moreover, some proposed materials for such insulation have undesirable attributes in battery manufacturing. Some insulating materials have a high tendency to shed particles, which is undesirable in that they cause dust and other problems in processes such as those requiring high speed automated application of adhesive tape onto the surface of the insulation. Particle shedding also affects the bond between the surface of the insulation and the adhesive tape, causing movement and / or misalignment of the insulation due to vibrations (such as road vibrations) experienced by most electric vehicles during normal operation.
[0004] What is needed is a firebreak construction that can provide improved thermal insulation, but that also does not have undesirable characteristics such as shedding. Summary of the Invention [Means for solving the problem]
[0005] The present invention relates to a paper suitable for use as an inter-cell flame breaker in a battery, and to a battery including the paper, the paper comprising: 40 to 70 weight percent fibrids; 30 to 60 weight percent mica, based on the total weight of the polymer and aerogel powder in the fibrids, 80 to 20 weight percent of a polymer; The blend includes 20 to 80 weight percent of the aerogel powder, and the paper has a thickness of 100 to 4000 micrometers. Yet another aspect of the present invention may be as follows. [1] A paper suitable for use as an inter-cell flame breaker in a battery, said paper comprising: 40 to 70 weight percent fibrids; 30 to 60 percent by weight of mica Including, said fibrids being, based on the total weight of polymer and aerogel powder in said fibrids, 80 to 20 weight percent of a polymer; Blended with 20 to 80 weight percent aerogel powder; Paper having a thickness of 100 to 4000 micrometers. [2] The fibrids are 60 to 40 weight percent of a polymer; The paper according to claim 1, comprising a blend of 40 to 60 weight percent aerogel powder. [3] 50 to 60 weight percent of fibrids; The paper according to [1] or [2] above, containing 40 to 50 weight percent mica. [4] The paper according to any one of [1] to [3], further comprising floc in an amount of up to 20 weight percent based on the total weight of the fibrids, mica, and floc in the paper. [5] The paper according to [4], wherein the floc is aramid floc. [6] The paper according to [5], wherein the aramid floc is poly(metaphenylene isophthalamide) floc. [7] The paper according to any one of [1] to [6], wherein the polymer is aramid. [8] The paper according to [7], wherein the aramid is poly(metaphenylene isophthalamide). [9] The paper according to any one of [1] to [8] above, having a thickness of 300 to 3000 micrometers.
[10] The paper according to any one of [1] to [9] above, having a tensile strength of 0.5 to 100 MPa.
[11] The paper according to any one of [1] to
[10] above, having a thermal conductivity of 0.015 to 0.05 W / mK.
[12] A battery comprising the paper according to any one of [1] to
[11] above. [Brief description of the drawings]
[0006] [Figure 1] 1 is a surface SEM photo image of paper made only from fibrids, where the fibrids were made from a blend of polymer and aerogel powder. [Diagram 2]1 is a surface SEM photographic image of a comparative paper made only from fibrids and aerogel powder. However, this paper was made by first making polymeric fibrids without any aerogel powder. The aerogel-free polymeric fibrids were then simply mixed with an appropriate amount of aerogel powder in water to make an aqueous headbox furnish for making the paper. [Diagram 3] 1 is a surface SEM photograph image of a comparative paper made only from fibrids, where the fibrids were made from a blend of polymer fibrids and activated carbon. [Figure 4] FIG. 2 is a surface SEM photographic image of a paper of the present invention made from a combination of mica and fibrids, where the fibrids were made from a blend of polymer and aerogel powder. [Diagram 5] 1 is a plot of the thermal conductivity of several papers made only from fibrids, where the fibrids are made from a blend of polymer and aerogel powder, showing the effect of different amounts of total aerogel powder in the fibrids on the thermal conductivity of the paper. [Figure 6] FIG. 1 is a cross-section of a calendered or densified paper made only from fibrids, where the fibrids were made from a blend of polymer and aerogel powder. [Figure 7] 1 is a surface SEM photo image of a calendered or densified paper made only from fibrids, where the fibrids were made from a blend of polymer and aerogel powder. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0007] The present invention relates to a paper suitable for use as an inter-cell fire break in a battery, the paper containing mica and a fibrid binder, the fibrid binder comprising a blend of polymer and aerogel powder, the paper having improved insulating and other properties over commercially available mica papers.
[0008] The paper comprises 40-70 weight percent fibrids and 30-60 weight percent mica based on the total weight of the fibrids and mica in the paper, the fibrids comprise a blend of 80-20 weight percent polymer and 20-80 weight percent aerogel powder based on the total weight of the polymer and aerogel powder in the fibrids, and the paper has a thickness of 100-4000 micrometers.
[0009] Multi-cell battery structures have battery cells arranged either in parallel or in series and are commonly known as battery blocks and battery packs. In these multi-cell battery structures, thermal energy from an abnormal thermal problem, such as a defect or failure, in one cell can propagate to adjacent cells. If the thermal problems are severe enough, they can propagate from cell to cell and cause a runaway thermal condition that can cascade to all cells in the battery block or pack, resulting in a fire or worse.
[0010] "Inter-cell insulation" is intended to include materials inserted between individual battery cells in a multi-cell battery structure that provide thermal insulation, i.e., they thermally isolate each battery cell and also tend to slow the transfer of thermal energy should a battery cell have an abnormal thermal problem, such as thermal runaway, that could result in a thermal "hot spot" or explosion.
[0011] The paper comprises a mixture of 40-70 weight percent aerogel-containing fibrids and 30-60 weight percent mica, based on the total weight of fibrids and mica in the paper. To protect adjacent battery cells from overheated cells, a better flame barrier and flame retardant insulation has low thermal conductivity as well as high dimensional stability at higher temperatures. When a thermal event occurs, the overheated cell temperature can rise to 800°C and above. However, adjacent cells should be kept below 200°C. Thus, the thermal insulation between adjacent cells is preferably sufficiently thermally stable up to at least 800°C.
[0012] In this paper structure, mica enhances fire barrier and dimensional stability. The flake shape of the mica platelets has anisotropic thermal conductivity (thermal conductivity in the z direction is 1 / 100 of that in the xy direction), and this property provides improved thermal insulation across the plane of the paper. It is believed that at least 30 weight percent mica is required in the paper to provide good dimensional stability. Although aramid fibrids shrink significantly at higher temperatures (above 200°C), it has surprisingly been found that when at least 30 weight percent mica is used in the paper structure, the paper structure is thermally stable and has essentially no shrinkage (meaning a change in length or width of + / - 5 percent or less at 200°C). In some embodiments, the paper comprises a mixture of 50-60 weight percent aerogel-containing fibrids and 40-50 weight percent mica.
[0013] Mica includes muscovite or phlogopite mica, or blends thereof, and may be calcined or uncalcined. As used herein, "calcined mica" refers to mica obtained by heating natural mica to high temperatures (usually above 800°C, sometimes above 950°C). This treatment removes water and impurities and improves the temperature resistance of the mica. Calcined mica is usually used in the form of flake particles, with muscovite type mica being preferred. As used herein, "uncalcined mica" refers to mica in its essentially high purity natural form, preferably homogenized and refined to remove defects and impurities. Uncalcined mica can form a highly porous mica layer due to the larger size of the natural mica flakes. The preferred mica is calcined mica due to its improved dielectric properties and corona resistance over uncalcined mica.
[0014] As used herein, the term fibrids refers to very small non-granular, fibrous or film-like particles, at least one of their three dimensions being an order of magnitude smaller than the largest dimension. These particles are prepared by precipitating a solution of a support material with a non-solvent under high shear, as disclosed, for example, in U.S. Pat. Nos. 2,988,782 and 2,999,788. Aramid fibrids are non-granular film-like particles of aromatic polyamides having a melting or decomposition point above 320° C. The preferred aramid fibrids are meta-aramid fibrids, and particularly preferred are fibrids made from meta-aramid poly(meta-phenylene isophthalamide) (MPD-I).
[0015] Fibrids generally have a maximum dimension length in the range of about 0.1 mm to about 1 mm with a length to width aspect ratio of about 5:1 to about 10:1. The thickness dimension is on the order of a fraction of a micron, e.g., about 0.1 micron to about 1.0 micron. Although not required, it is preferred to incorporate the aramid fibrids into the paper while they are in a wet state. As used herein, "fibrid" and "fibrid binder" are used interchangeably.
[0016] The fibrids comprise a blend of 80-20 weight percent polymer and 20-80 weight percent aerogel powder, based on the total weight of the polymer and aerogel powder in the fibrids. The aerogel powder has a high surface area (600-800 m 2 / g). A specific ratio of polymer to aerogel polymer is required to consolidate the aerogel powder within the fibrids. Without proper bonding between the aerogel powder and the polymer, the unconsolidated aerogel powder can result in air bubble formation and dust generation during the papermaking process. Therefore, it is believed that the minimum amount of polymer required to adequately consolidate the aerogel powder is 20 weight percent. Also, at least 20 weight percent aerogel powder is required within the fibrid structure to provide the desired lower thermal conductivity. In some embodiments, the fibrids include a blend of 60-40 weight percent polymer and 40-60 weight percent aerogel powder.
[0017] Aerogel refers to a porous, extremely lightweight synthetic material derived from a gel, where the liquid component of the gel has been replaced with a gas. The result is a solid with extremely low density and low thermal conductivity. Aerogels can be made from a variety of compounds, but silica aerogel is the preferred and most common type of aerogel.
[0018] As used herein, the terms "aerogel", "aerogel powder", and "aerogel particles" are used interchangeably and refer to the preferred aerogels which are highly porous, hydrophobic, high surface area, preferably amorphous silica particles or granules having a particle size range of 10 nanometers to 50 micrometers (0.00001 to 0.05 millimeters), preferably 0.05 to 20 micrometers. Generally, they are chemically similar to common fumed silica products, but have higher porosity (>95%), lower density (0.03 to 0.1 g / cm). 3 ), small average pore diameter (20 nm), lower thermal conductivity (0.017–0.022 W / mK), higher surface area (600–800 m 2 / g), higher surface area, and larger pore volume, and are typically produced by a sol-gel manufacturing process. Pioneering patents describing aerogels include U.S. Patent Nos. 2,093,454, 2,188,007, and 2,249,767 to Kistler, with more recent disclosures available such as U.S. Patent Nos. 8,518,335 and 8,961,919 to Joung et al.
[0019] FIG. 1 is a surface SEM photographic image of a paper made only from fibrids, where the fibrids were made from a blend of polymer and aerogel powder. In this case the paper has 50 weight percent MPD-I polymer and 50 weight percent aerogel powder throughout. That is, a polymer solution containing a mixture of polymer and aerogel powder is subjected to a fibridator or other device that aggressively shears the polymer solution in the presence of a non-solvent, typically water, to produce fibrids from the mixture of polymer and aerogel powder. These fibrids, or the dispersion used to make fibrids containing fibrids, are then used to make an aqueous headbox furnish. The furnish can then have other additives and water can be added or removed to obtain the desired consistency. The furnish containing the dispersion of aerogel-containing fibrids is provided to, or poured onto, a screen and paper is made from the solids of the dispersion.
[0020] Figure 1 surprisingly shows the interaction or fibrid formation around the aerogel particles at a magnification of 10 micrometers. The aerogel particles 1 are held in place in the paper by polymer tentacles 2, forming web-like connections between the aerogel and the fibrids in the paper structure. This provides a paper with no or reduced dusting potential. Furthermore, the surface of the paper has a smooth, non-grainy feel indicating improved adhesion of the aerogel particles in the sheet.
[0021] FIG. 2 is a surface SEM photographic image of a comparative paper made only from fibrids and aerogel polymer, the paper also having 50 weight percent MPD-I polymer fibrids and 50 weight percent aerogel powder throughout. However, this paper was made by first making the polymer fibrids without any aerogel. In that case, the aerogel-free polymer fibrids were simply mixed with an appropriate amount of aerogel powder in water to make the aqueous headbox furnish. That is, the dispersion of fibrids and aerogel particles in water was then screened to make the paper. As can be seen in the 10 micrometer magnification photographic image, there is no measurable bonding of the aerogel particles 3 to the fibrids 4. Thus, little can be done to prevent aerogel particle dust from forming with the paper. Furthermore, the surface of the paper had a rough, grainy feel, indicating a lack of aerogel particle adhesion.
[0022] FIG. 3 is a surface SEM image of a comparative paper made only from fibrids, where the fibrids are made from a blend of polymer and activated carbon, the fibrids also having 50 weight percent MPD-I polymer fibrids and 50 weight percent activated carbon powder throughout. The activated carbon was type PCB-G obtained from Calgon Carbon Corp. of Pittsburg, Pa. This paper was made by a similar process to the paper shown in FIG. 1, i.e., a polymer solution containing a mixture of polymer and carbon black powder was fed to a fibridator, fibrids were made from the mixture, and then these fibrids containing carbon black were used to make an aqueous headbox furnish. That is, a dispersion of carbon black-containing fibrids in water was then fed to a screen to make paper. The surface SEM image shows that the surface structure of this paper is very different from the aerogel-containing fibrid paper. The activated carbon 5 is not attached by polymer tentacles, but is encapsulated by a fibrid polymer as described in U.S. Patent No. 5,482,773 to Bair, which is believed to indicate that the low density of the aerogel polymer causes these particles to adhere much more strongly to the polymer structure than activated carbon.
[0023] Figure 4 is a surface SEM photographic image of a paper of the invention made from a combination of mica 7 and fibrids, the fibrids being made from a blend of polymer and aerogel powder 6. The aerogel particles are held in place by the polymer tentacles, forming web-like connections between the aerogel and the fibrids in the paper structure. The mica flakes are several orders of magnitude larger than the aerogel particles, so the image is shown at a magnification of 50 micrometers.
[0024] The paper has a thickness of 100-4000 micrometers (0.1-4 millimeters). The minimum gap between cells (either pouch or prismatic cells) is approximately 0.1 mm, allowing current battery design standards and battery cell and module designers to miniaturize battery pack designs as much as possible due to the limited space inside electric vehicles. Therefore, a gap of more than 4 mm between two cells is generally undesirable. In some embodiments, the paper has a thickness of 300-3000 micrometers (0.3-3 millimeters). In some embodiments, the paper can have a basis weight of 50-500 grams per square meter. In some embodiments, the paper has a basis weight of 100-300 grams per square meter.
[0025] As an optional embodiment, the paper containing mica and aerogel powder fibrid binder can further include floc present in an amount as much as 20 weight percent (i.e., 0-20 weight percent) based on the total weight of the fibrids, mica, and floc in the paper. In some embodiments, 5-15 weight percent floc is desired in the paper, based on the total weight of the fibrids, mica, and floc in the paper.
[0026] The term floc as used herein means fibers having a short length and commonly used in the preparation of wet laid sheets and / or papers. Typically, the floc has a length of about 3 to about 20 millimeters. The preferred length of the floc is about 3 to about 7 millimeters. Floc is usually produced by cutting continuous fibers to the required length using methods known in the art. A preferred floc is aramid floc, i.e., floc produced from aramid polymer fibers. A preferred aramid floc is poly(metaphenylene isophthalamide) (MPD-I) floc.
[0027] The term aramid as used herein means an aromatic polyamide in which at least 85% of the amide (-CONH-) bonds are directly attached to two aromatic rings. Additives may be used with the aramid and may be dispersed throughout the polymer structure. It has been discovered that up to about 10 weight percent of other support materials can be blended with the aramid. It has also been discovered that copolymers having up to about 10 percent of other diamines replacing the diamines of the aramid or up to about 10 percent of other diacid chlorides replacing the diacid chlorides of the aramid can be used.
[0028] The preferred polymers for both the fibrids and the optional floc are aramid polymers, specifically meta-aramid polymers for both the fibrids and the optional floc. An aramid polymer is considered to be meta-aramid when two rings or radicals are oriented meta to each other along the molecular chain. The preferred meta-aramid for both the fibrids and the optional floc is poly(meta-phenylene isophthalamide) (MPD-I). U.S. Pat. Nos. 3,063,966, 3,227,793, 3,287,324, 3,414,645, and 5,667,743 describe useful methods for producing aramid fibers that can be used to produce aramid floc.
[0029] Alternatively, the aramid floc can be a para-aramid or an aramid copolymer. An aramid polymer is considered to be para-aramid when two rings or radicals are oriented para to each other along the molecular chain. Methods for producing para-aramid fibers are generally disclosed, for example, in U.S. Pat. Nos. 3,869,430, 3,869,429, and 3,767,756. One preferred para-aramid is poly(paraphenylene terephthalamide), and one preferred para-aramid copolymer is copoly(p-phenylene / 3,4' diphenyl ester terephthalamide).
[0030] Specifically, a commercially suitable process for making the paper of the present invention containing aerogel-containing fibrids and mica and optional floc in a papermaking machine may include feeding an aqueous dispersion containing the mica and fibrous materials in the desired amounts and ratios into the headbox of the papermaking machine, then uniformly wet-laying and dispersing these solids as a web onto a papermaking wire, and removing most of the liquid water. The wet web can then be dried on a dryer drum to form paper. In some embodiments, the paper can be further calendered or pressed under pressure and heat in the nip of a hot roll calender or by other means to consolidate and densify the paper into a layer having the desired thickness and properties. If necessary, two or more lighter basis weight or thinner wet webs of the same composition can be produced separately and then calendered together to consolidate into a single layer.
[0031] Figures 6 and 7 are cross-sectional and surface views, respectively, at 500 micrometer and 10 micrometer magnifications, of a calendered paper made only from fibrids (where the fibrids are made from a blend of polymer and aerogel powder). They show that at least some of the surprising interactions or fibrid formation around the aerogel particles are maintained in the sheet after densification. The aerogel particles 11 are held in place within the paper by polymer tentacles 12, forming web-like connections between the aerogel and the fibrids in the paper structure.
[0032] Representative equipment and machinery that can be used to make paper include, for example, but are not limited to, continuous processing equipment such as a Fourdrinier or inclined wire machine, or batch processing equipment such as equipment that makes paper manually in a handsheet form that includes a forming screen. For a general process of forming aramid materials into paper, reference can be made to U.S. Patent No. 3,756,908 to Gross and U.S. Patent No. 5,026,456 to Hesler et al.
[0033] In some embodiments, the paper has a tensile strength of 0.5 to 100 megapascals (MPa). In some applications, it is desirable for the paper to have a tensile strength of at least 15 megapascals or more. For example, it is believed that the paper requires this level of tensile strength to withstand some battery manufacturing processes, which may include the cell winding process (winding the separator with the current collectors, anode and cathode). The tensile strength also contributes to the flame shielding of the separator during use. Paper tensile strengths above 100 megapascals do not have adverse effects, but the parameter reaches a point where the value is reduced. Thus, in some preferred embodiments, the paper has a tensile strength of 15 to 50 megapascals. In some embodiments, the paper has a tensile strength of 15 to 100 megapascals.
[0034] In some embodiments, the paper has a thermal conductivity of 0.015 to 0.05 Watts per meter Kelvin (W / mK). To effectively prevent heat propagation, paper with a lower thermal conductivity that is stable over a wide range of operating temperatures, such as battery operating temperatures (-40°C to 80°C), and up to thermal hotspot temperatures (800°C to 1,000°C), is preferred. In some embodiments, the paper has a thermal conductivity of 0.015 to 0.04 W / mK.
[0035] In some embodiments, a 1 mm (+ / - 30%) thick paper comprising mica and aerogel-containing fibrids exhibits a TPP flame performance of at least 10 seconds to the equivalent of a second degree burn as measured by the Thermal Performance Protection Test (TPP), and in some embodiments, the paper exhibits a TPP flame performance of at least 12 seconds to the equivalent of a second degree burn.
[0036] It is believed that there is a synergistic effect on the thermal and mechanical properties of the resulting paper from the combination of mica and aerogel-containing fibrids. The paper of the present invention shows a definite increase in voltage resistance with increasing mica content, but also a definite decrease in mechanical strength and toughness (tensile strength and elongation). However, increasing the amount of aerogel powder in the fibrids improves thermal insulation (lower thermal conductivity) and provides better flame protection (TPP). In some cases, the paper of the present invention containing a combination of mica and aerogel-containing fibrids has almost half the thermal conductivity (i.e., twice the insulating properties) while providing twice the thermal protection (TPP) when compared to paper made by simply mixing mica, aerogel, and fibrids together and making paper. These significant properties, as well as the significant improvement in shedding problems, indicate that these papers are suitable for use as battery thermal insulation and firebreaks (cell-to-cell, cell-to-module, module and pack interiors, etc.).
[0037] Batteries including the paper described herein can be manufactured by using the paper as an insulation between cells, i.e., inserting the paper between individual battery cells in a multi-cell battery structure to provide a fire shield and thermal insulation between the individual battery cells. Exemplary battery types include, but are not limited to, multi-cell battery structures having battery cells arranged in either parallel or series, commonly known as battery blocks and battery packs. However, other batteries including the paper described are possible, since the paper is intended to thermally isolate each battery cell and retard the transfer of heat energy and / or flame from one cell to another cell or structure.
[0038] Test Method The following test methods were used in the examples provided below.
[0039] Thickness: 5N / cm 2 The measurements were made according to TAPPI 411 using the weight of the material and recorded in mm.
[0040] Basis weight is measured according to ASTM D 645 and ASTM D 645-M-96 and is in g / m 2 Recorded in units.
[0041] Tensile strength was measured according to ASTM D 828-93 using a 2.54 cm wide specimen and a gauge length of 18 cm and was reported in N / cm or MPa.
[0042] The dielectric strength was measured according to ASTM D D149-97A and reported in kV / cm.
[0043] Thermal conductivity was measured according to ASTM E1530 and reported in W / mK.
[0044] The Thermal Performance Protection Test (TPP) is a measure of the flammability performance of material fabrics and sheets, providing realistic conditions of exposure to a combination of radiant and convective heat. Specimens are exposed to conditions typical of a flame: 84 kW / m 2 (2cal / cm 2 A constant combination of 50% radiant heat and 50% convective heat at a constant heat flux of 80kW / m2 / s. The test then measures the time it takes for the temperature and energy transferred to the back of the fabric to reach a level equivalent to a second degree burn if the material were to be worn, as well as the amount of thermal energy per surface area (TPP value). The TPP test method used is 80kW / m2. 2 This test method has been adopted by ISO as a test method standard (ISO 17492) using a heat flux exposure of 84 kW / m. However, the US NFPA 1971 standard uses a heat flux exposure of 84 kW / m. 2 This requires the ISO 17492 test to be performed with a modified, increased heat flux exposure of 1000 Hz, and this higher heat flux is used here. EXAMPLES
[0045] Example 1 Aerogel-aramid fibrid paper with lower thermal conductivity and higher flame resistance was produced. A dispersion of polymer in solvent containing aerogel powder particles was produced by combining 65 parts by weight of the solvent dimethylacetamide, 15 parts by weight of poly(metaphenylene isophthalamide) (MPD-I) polymer, 5 parts by weight of calcium chloride as a solubility enhancer, and 15 parts by weight of aerogel powder (Type IC 3100 Enova® aerogel obtained from Cabot Corp., Boston, MA) in a kettle with stirring until a homogenous mixture was obtained. The mixture was then slowly poured into a vigorously stirring Waring blender, which simultaneously solidified the polymer from the solvent into a membrane-like fibrid, where the MPD-I polymer and aerogel powder were present in a 1:1 ratio, and is referred to as item 1-1. The resulting fibrids were collected on a Buchner funnel as a wet laid paper and washed with deionized water until all the fibrids were thoroughly washed into the funnel. The paper was then dried and the dried paper exhibited a smooth, grain-free surface. As shown in Figure 1, the aerogel powder particles were anchored to the fibrids by the polymer tentacles around the particles.
[0046] This was repeated three more times, except that the amount of aerogel powder was reduced each time to form fibrids with MPD-I polymer:aerogel ratios of 1.0:0.75, 1:0:0.5, and 1:0.25, which were designated items 1-2, 1-3, and 1-4, respectively. To analyze the different amounts of silicate, and therefore the amount of aerogel immobilized in all four fibrid samples, TGA thermogravimetric analysis (TGA) was performed on all items using a high resolution TA Instruments Q500TGA (40-700C) in air. The results are shown in Table 1, which indicates that the aerogel powder particles were immobilized in the fibrid polymer.
[0047] [Table 1]
[0048] Thermal conductivity was then measured on these paper samples by the thin film method using a transient planar heat source (TPS1500) using 2.45 kg pressure on a 2 inch diameter laminate sample. The effect of aerogel particles on the thermal conductivity (TC) of the composite structure is shown in the graph of Figure 5, compared to a control paper sample of polymer fibrids with no aerogel (0 wt%). It was found that the addition of just over 40 weight percent aerogel particles reduced the thermal conductivity from 0.054 W / mK to 0.028 W / mK.
[0049] Example 2 Paper containing both mica and aerogel-containing MPD-I fibrids was produced, which has lower thermal conductivity and higher flame resistance. Four separate aqueous dispersions were produced as in Example 1, each containing one of the four fibrid samples of Example 1. A weighted amount of calcined mica flakes was added separately to each dispersion. The mica was a muscovite type available from Electrical Samica Flake Co., Rutland, Vermont. In addition, another dispersion was produced by blending fibrids without aerogel (100% MPD-I fibrids), mica, and aerogel powder for the control handsheet. The relative amounts of each component of the inventive and comparative papers are listed in Table 2.
[0050] [Table 2]
[0051] Each aqueous dispersion was poured into a 21 x 21 cm handsheet mold with 8 liters of water to form four wet-laid sheet papers designated 2-1 to 2-4. The handsheets were then placed separately between two pieces of blotter paper, hand couched with a cotton swab, and dried in a handsheet dryer at 150°C for 10 minutes. The dried papers showed a smooth, grain-free surface. The physical and thermal properties of the handsheets (described in the Test Methods) are shown in Table 3.
[0052] Comparative example A Comparative Paper A was made by combining 2 grams of aerogel powder in water with 4 grams of aerogel-free MPD-I fibrids, produced by the method generally described in U.S. Pat. No. 3,756,908, and 4 grams of calcined mica flakes to form an aqueous dispersion. The aqueous dispersion was then used to form handsheets as in Example 2. The dried paper exhibited a rough, de-grained surface. The physical and thermal properties are shown in Table 3. TGA (thermogravimetric analysis) of the dried paper showed that a residual amount of aerogel particles weighing about 1.75 grams remained, which means that nearly 30% of the original aerogel powder was lost during the papermaking process. The data in Table 3 show the synergistic effect on the thermal and mechanical properties of the paper resulting from the combination of mica and aerogel-containing fibrids. The paper shows a significant increase in voltage endurance with increasing mica content, but also a significant decrease in mechanical strength and toughness (tensile strength and elongation). However, increasing the amount of aerogel powder in the fibrids improves thermal insulation (reduced thermal conductivity) as well as providing better fire protection (TPP). Both Comparative Example A and Examples 2-3 papers were made using 20 weight percent aerogel powder. However, the papers of Examples 2-3 have nearly half the thermal conductivity (i.e., twice the insulating properties) and twice the thermal protection (TPP) of the paper of Comparative Example A. These significant properties, as well as the significant improvement in shedding problems, indicate that these papers are suitable for use as battery thermal insulation and fire protection (cell-to-cell, cell-to-module, module and pack interiors, etc.).
[0053] [Table 3]
[0054] Example 3 Example 2 was repeated to produce a mica and aerogel-containing fibrid paper designated 3-1, which further contained floc, exactly as in Example 2-2, except with 10 weight percent mica and Nomex® floc (Nomex® fibers with a linear density of 0.22 tex and a length of 0.64 cm, available from DuPont Co., Wilmington, Del.). The addition of floc helped improve the thermal conductivity to 0.025 W / mK, but the voltage resistance was slightly reduced to 200 kV / cm.
[0055] Three more mica, aerogel-containing fibrid, and floc containing papers of various compositions, designated 3-2, 3-3, and 3-4, were then prepared in a similar manner and tested for burn performance. All dried papers exhibited smooth, grain-free surfaces. The compositions and test results are shown in Table 4.
[0056] [Table 4]
Claims
1. 1. A paper suitable for use as an inter-cell flame breaker in a battery, said paper comprising: 40 to 70 weight percent fibrids; 30 to 60 weight percent mica; Including, said fibrids being, based on the total weight of polymer and aerogel powder in said fibrids, 80 to 20 weight percent of a polymer; Blend with 20 to 80 weight percent aerogel powder; The paper has a thickness of 100 to 4000 micrometers.
2. 10. The paper of claim 1 further comprising floc in an amount of up to 20 weight percent based on the total weight of the fibrids, mica, and floc in the paper.
3. 3. The paper of claim 1 or 2, wherein the polymer is an aramid.
4. The paper according to any one of claims 1 to 3, having a thickness of from 300 to 3000 micrometers.
5. A battery comprising the paper according to any one of claims 1 to 4.
Citation Information
Patent Citations
Aramid complex sheet, preparation thereof and electric and electronic equipment and appliances having the same
JP1998130496A
Flame resistant barrier paper composition
JP2003520310A
Composite sheets and cargo containers containing them
JP2017519656A
Corona resistant resin compatible laminate
JP2018519195A
Fire resistant back-sheet for photovoltaic module
US20120312366A1
